2023
DOI: 10.1002/epi4.12716
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of FKBP5 single‐nucleotide polymorphisms in functional seizures

Abstract: Objective We investigated the associations between FKBP5 single‐nucleotide polymorphisms (SNPs) and functional seizures (FS). Methods Seventy patients with FS, 140 with major depressive disorder (MDD), and 140 healthy controls were studied. Their DNAs were analyzed for the rs1360780 in the 3′ region and rs9470080 in the 5′ region of the FKBP5. Childhood trauma questionnaire and hospital anxiety and depression scale were used. Results Patients with FS and those with MDD had less GG and more AA genotypes in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…18,19 In one recent study, the authors showed that the hypothesis of the association between FKBP5 single nucleotide polymorphisms (SNPs) and FS is a plausible hypothesis. 20 In that study, patients with FS had less GG and more AA genotypes in both rs9470080 and rs1360780 SNPs compared with healthy controls. However, they could not show whether FKBP5 polymorphisms were associated with FS in the absence of depression.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…18,19 In one recent study, the authors showed that the hypothesis of the association between FKBP5 single nucleotide polymorphisms (SNPs) and FS is a plausible hypothesis. 20 In that study, patients with FS had less GG and more AA genotypes in both rs9470080 and rs1360780 SNPs compared with healthy controls. However, they could not show whether FKBP5 polymorphisms were associated with FS in the absence of depression.…”
Section: Introductionmentioning
confidence: 79%
“…In that study, patients with FS had less GG and more AA genotypes in both rs9470080 and rs1360780 SNPs compared with healthy controls. However, they could not show whether FKBP5 polymorphisms were associated with FS in the absence of depression 20 . Another study showed that patients with FS have basal hypercortisolism that is independent of the acute occurrence of seizures 21 .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…To the Editor, Recently, we published a paper that suggested that FKBP5 single-nucleotide polymorphisms may play a role in functional seizures (psychogenic nonepileptic seizures/attacks). 1 We also published another paper entitled "FKBP5 blockade may provide a new horizon for the treatment of stress-associated disorders: An in-silico study" providing a list of the currently available and approved drugs (e.g., fluticasone propionate, prednisolone, dexamethasone, mirtazapine, sertraline, fluoxetine, and citalopram) that could potentially be used for this purpose. 2 More recently, I read an article entitled: "Cannabidiol alleviates neuroinflammation and attenuates neuropathic pain via targeting FKBP5."…”
mentioning
confidence: 99%